Metformin Induces Apoptosis through AMPK-Dependent Inhibition of UPR Signaling in ALL Lymphoblasts - Leclerc, Gilles M.; Leclerc, Guy J.; Kuznetsov, Jeffim N.; DeSalvo, Joanna; Barredo, Julio C. (PloS one, 2013)
The outcome of patients with resistant phenotypes of acute lymphoblastic leukemia (ALL) or those who relapse remains poor. We investigated the mechanism of cell death induced by metformin in Bp- and T-ALL cell models and primary cells, and show that metformin effectively induces apoptosis in ALL cells. Metformin activated AMPK, down-regulated the unfolded protein response (UPR) demonstrated by significant decrease in the main UPR regulator GRP78, and led to UPR-mediated cell death via up-regulation of the ER stress/UPR cell death mediators IRE1α and CHOP. Using shRNA, we demonstrate that metformin-induced apoptosis is AMPK-dependent since AMPK knock-down rescued ALL cells, which correlated with down-regulation of IRE1α and CHOP and restoration of the UPR/GRP78 function. Additionally rapamycin, a known inhibitor of mTOR-dependent protein synthesis, rescued cells from metformin-induced apoptosis and down-regulated CHOP expression. Finally, metformin induced PIM-2 kinase activity and co-treatment of ALL cells with a PIM-1/2 kinase inhibitor plus metformin synergistically increased cell death, suggesting a buffering role for PIM-2 in metformin's cytotoxicity. Similar synergism was seen with agents targeting Akt in combination with metformin, supporting our original postulate that AMPK and Akt exert opposite regulatory roles on UPR activity in ALL. Taken together, our data indicate that metformin induces ALL cell death by triggering ER and proteotoxic stress and simultaneously down-regulating the physiologic UPR response responsible for effectively buffering proteotoxic stress. Our findings provide evidence for a role of metformin in ALL therapy and support strategies targeting synthetic lethal interactions with Akt and PIM kinases as suitable for future consideration for clinical translation in ALL.